Nearshore Zone Dynamics Determine Pathway of Organic Carbon From Eroding Permafrost Coasts. Issue 15 (31st July 2020) - Jong, Dirk; Bröder, Lisa; Tanski, George; Fritz, Michael; Lantuit, Hugues; Tesi, Tommaso; Haghipour, Negar; Eglinton, Timothy I.; Vonk, Jorien E.
Abstract: Collapse of permafrost coasts delivers large quantities of particulate organic carbon (POC) to Arctic coastal areas. With rapidly changing environmental conditions, sediment and organic carbon (OC) mobilization and transport pathways are also changing. Here, we assess the sources and sinks of POC in the highly dynamic nearshore zone of Herschel Island‐Qikiqtaruk (Yukon, Canada). Our results show that POC concentrations sharply decrease, from 15.9 to 0.3 mg L −1, within the first 100–300 m offshore. Simultaneously, radiocarbon ages of POC drop from 16, 400 to 3, 600 14 C years, indicating rapid settling of old permafrost POC to underlying sediments. This suggests that permafrost OC is, apart from a very narrow resuspension zone (<5 m water depth), predominantly deposited in nearshore sediments. While long‐term storage of permafrost OC in marine sediments potentially limits biodegradation and its subsequent release as greenhouse gas, resuspension of fine‐grained, OC‐rich sediments in the nearshore zone potentially enhances OC turnover. Plain Language Summary: The coast around the Arctic Ocean consists mostly of permafrost, permanently frozen ground, which contains large amounts of millennia‐old organic carbon. Due to rising temperatures, this several thousand years old organic carbon is released to the Arctic Ocean at an increased rate by permafrost thaw and coastal erosion. Once released, organic carbon can be degraded and emitted as greenhouse gas to the atmosphere, or it can be stored away in marine sediments. In this study, we find that this old organic carbon quickly settles after release into the ocean and is buried in sediments close to shore, whereas the overlying sea water is dominated by young organic carbon from other sources than permafrost. However, sediments close to shore can be reworked by waves and currents, releasing the organic carbon again. This makes the zone closest to shore an important research area to assess the impact of thawing permafrost on climate. Key Points: Suspended particulate organic carbon (POC) sharply decreases in age and concentration within the nearshore zone Beyond a narrow resuspension zone, permafrost‐derived OC dominates surface sediments, whereas much younger OC is found in the water column Permafrost‐derived POC is rapidly removed from the water column, showing the critical role of nearshore dynamics for OC transport